Strategi Meningkatkan Keberdayaan Keluarga Miskin Pedesaan - R. Toha; A. Saleh (Institut Pertanian Bogor, 2010)
Poor rural families were part of rural society which need to improved was resources, in order that they could effordto run family function, had creativity in economy, social, physicology and sociology, that kind of creativity, poorfamilies hopefully could build harmonies in their life. These research had correlation descriptive character whichpurposes; (a) analyzing factors that cause poverty, (b) analyzing characteristic of poor families from social economyaspect, physical characteristic, physicology characteristic and sociology characteristic (c) knowing and analyzingdependability pattern of triggering factors and characteristic of poor families in promoting capability of poorfamilies (c) building strategies to promote capability of poor families according to trigger factor and characteristicof rural poor families. Research result showed internal environment and external factors which influenced capabilityof poor families in rural area. Trigger factor that emerge poor families were, poverty was already inherit by theirelderly, because their elderly didn’t have wide farmland, low education background (they didn’t pass the elementaryschool in average), didn’t have other skills beside farming. There were obvious correlation among social economy,social capital, local intelegence and capability of poor families. According to data and information that acquiredfrom the research. Therefore strategic concept was made and pointed, empowering competence of personalimplementer of government program in subdistrict level empowering poor families competence, promoting poorfamilies participation in government and private programs that operation in rural area. Build poor families networkwith business world in marketing their farm product and giving them facilitation to get capital, seeds and tools thataccording to compete development that given to poor peoples.